PERAN BAURAN PROMOSI PADA KEPUTUSAN PEMBELIAN - Bayu Kurniawan; Ahmad Dwi Nurdiyanto; Hesti Respatiningsih (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to analyze the effect of the promotion mix on consumer purchasing decisions of CV. Com Focus Display. The type of research used in this study uses a quantitative approach method with comparative causal analysis. Samples were taken from the entire population of CV consumers. Focus Display Com uses purposive sampling. Either partially or simultaneously that the variables of advertising, sales promotion, personal selling and direct marketing have a positive and significant effect on purchasing decisions. The promotion mix has an influence on purchasing decisions by 65.1%.